Hidden premises in an argument by Deng Xi: the action of pragmatics according to the syntactic theories - López-Astorga, Miguel (Círculo de Lingüística Aplicada a la Comunicación, 2017)
The syntactic theories trying to describe human reasoning, communication, and language often claim that the role played by pragmatics basically consists of providing hidden premises that help one draw conclusions. Obviously, this is a very strong assumption. However, this paper is intended to show that there are arguments used by people that cannot be understood without such premises, and that hence they confirm that assumption. This is done by resorting, as an example, to an argumentation given by the Chinese thinker Deng Xi.